QUALITY CONTROL IN THE CONSTRUCTION OF REINFORCED CONCRETE BUILDINGS IN DAR ES SALAAM - Rubaratuka, I A (Tanzania Journal of Engineering and Technology, 2018)
Quality Control in the construction industry is very important to ensure that what is being done conforms to the applicable standards or good practice and the contract documents. In this article, results of investigations conducted at different construction sites for reinforced concrete buildings in Dar es Salaam to check if quality control measures are being implemented are discussed. It has been established that generally quality control is not properly carried out. Finally, measures to enhance quality control on sites are outlined.